Global landscape of COVID-19 and epilepsy research: A bibliometric analysis - Wang, Guangxin; Bai, Lian; Zhao, Mingxue; Wang, Shumei (Frontiers in Neurology, 2022)
Background: A large number of papers regarding coronavirus disease 2019 (COVID-19) and epilepsy have been published since the declaration of the COVID-19 pandemic. However, there is no bibliometric analysis on these papers. In this study, we aimed to analyze the bibliometric characteristics of these papers, thus identifying the trends and future directions of COVID-19 and epilepsy research. Methods: Scientific papers regarding COVID-19 and epilepsy were retrieved through searches of the Web of Science Core Collection database. Title, authors, contributing institute, country, source journal, times cited, and additional information were extracted from each selected paper. Microsoft Excel 2019 and GraphPad Prism 8 were used to analyze the extracted data and export the bar charts and tables whilst VOSviewer software was used to perform and visualize co-authorship analysis and co-occurrence analysis of keywords. Results: A total of 317 papers regarding COVID-19 and epilepsy were included in the final analysis. Epilepsy & Behavior published the largest number of papers (n = 84). J. Helen Cross and Naoto Kuroda were the most prolific authors (n = 13 each). The United States (n = 88) and the University of London (n = 23) were the country and organization with the most contributions, respectively. The strongest authors’ collaborations were between Giovanni Assenza and Jacopo Lanzone and between J. Helen Cross and Nathalie Jette. Selected author keywords were organized into seven clusters, and the keywords in clusters 1 and cluster 4 had the largest average appearing year of any clusters. Conclusion: This is the first bibliometric analysis of papers regarding COVID-19 and epilepsy. Our results showed that the United States was the leading country whilst J. Helen Cross was the most influential scholar in COVID-19 and epilepsy research. psychological consequences of COVID-19, and the safety of COVID-19 vaccines for people with epilepsy, are possible areas for future research on COVID-19 and epilepsy.